ADMINISTRATIVE SUPERVISION OVER THE ACTIVITIES OF THE CITY SELF-GOVERNMENTS OF THE EKATERINOSLAV PROVINCE (1870 – 1913) - Вадим Коробка; Юлія Коробка (Cхід)
The article reveals the importance of administrative supervision over city self-governments in the Ekaterinoslav Province (1870-1913). Their social orientation has been established. Expenses provided a priority increase in expenditures on schooling and medi-cine, veterinary and sanitary units. State control institutions generally did not interfere with the budget policy of municipal self-government institutions and its humanitarian component, although misunderstandings sometimes arose. It has been revealed that the implementation of state control over public administrations in the Ekaterinoslav Province often faced the aspirations of self-government bodies in secondary issues of municipal organization which were incompatible with the law in the opinion of its hosts. Disputes arose mostly on the basis of different understandings of the rules of sale and purchase of goods, measures to regulate traffic on city streets etc. It has been confirmed that in exercising their powers in the field of control over the comp-liance with the law by city self-governments, state institutions of the provincial level some-times showed inappropriate competence in the field of interpretation of imperial legislation, which resulted in erroneous decisions. Certain decisions of public administrations of cities also sometimes violated imperial law and were subject to unconditional termination or revocation. It has been proved that the public administrations of the Province widely used the legally regulated opportunity to defend their decisions in the Senate. The specific Senate cases started in connection with the supervision over the legality of decisions of city self-governments and the provincial presence for the zemstvo and city affairs give the impression that they were considered on the basis of a qualified verification of compliance with imperial law. It has been established the administrative control was implemented slowly, and formula-tions of thoughts on appealing the decisions of the Provincial Presence were deprived of speed and efficiency. The provincial zemstvo sinned against evading operative decisions. At the same time, there was a dishonest delay in the circulation of documents in all parts of public administ¬ration and local self-government.